Lessons from the COVID-19 situation: Rethinking global supply chain networks and strengthening supply management in public procurement in Germany - Marc Helmold; Matthias Einmahl; Klaus Joachim Rassmann; Luciano N. Carvalho (IUBH Internationale Hochschule, 2020)
The COVID-19 crisis has identified several weaknesses and shortcomings of global supply chain networks. Due to the rapidly increasing demand of protective healthcare equipment, i.e. goggles, masks or equipment, it is visible that global supply chains have been significantly challenged. Furthermore, countries had to compete for available products, also leading to drastic price rises. The German government had to ask Multinational Companies (MNC) to procure healthcare equipment, as government procurement authorities were not experienced in dealing with global supply chains (Petersen, 2020). Moreover, even though machines for making masks and healthcare equipment are manufactured in Germany, there was no domestic supply. Under pressure to overcome the masks shortage in Germany, the government has promised state subsidies covering 30% of investment costs of companies venturing to launch fabric production. The funding will be capped at exteuro10 million (10.9 million), but includes a purchase guarantee from the government. The situation displayed how fragile and disruptive global supply chains can be in crisis situations. Moreover, the case shows the dependency on imports from China and other countries for pharmaceuticals or medical equipment.
Keywords: L91; L98; R41; R48; 650; Public Procurement; Supply Chain Management (SCM); Procurement Strategy; Public Sourcing